A method for modifying a fragmented pre-dispersed aerogel powder

CN122916602APending Publication Date: 2026-10-16GUIZHOU AEROSPACE WUJIANG MACHINERY & ELECTRICITYEQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611276856.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

1.粉体分散性差、遮光改性效果不稳定:碳化硅、二氧化钛等遮光粉体粒径微小、表面活性高,直接掺杂极易发生团聚,难以均匀渗透进入完整纤维气凝胶的微小纳米孔隙内部,绝大部分粉体仅附着于材料表面,造成气凝胶局部辐射传热抑制不均,高温隔热性能波动大,批次一致性差,无法实现稳定的红外遮光改性效果

Benefits of technology

显著提升粉体分散均匀性:通过粉体预分散预处理破除超细粉体的原生团聚,配合碎片化纤维絮片的浸润复合,使改性粉体以单颗粒状态均匀嵌合于纤维絮片的内外孔隙与气凝胶三维网络中,避免传统工艺中粉体表层富集、局部团聚的问题,实现粉体掺杂改性效果在材料整体空间内的均匀发挥。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916602A_ABST
    Figure CN122916602A_ABST
Patent Text Reader

Abstract

The application discloses a kind of fragmentary pre-dispersed aerogel powder modification preparation methods, which sequentially passes through powder pre-dispersed pretreatment, fiber flocculation piece infiltration composite, gradient gel forming by pressurization, fractional solvent replacement soaking, the continuous process of supercritical drying and shaping, modified powder is uniformly embedded in the three-dimensional pore of fragmentary fiber flocculation piece.The application breaks through the process limitation of traditional complete fiber base material direct doping, solves the problem of powder agglomeration uneven dispersion, weak interfacial bonding force, easy to fall off, modification effect and mechanical property imbalance, can simultaneously improve the functionality, structural stability and batch consistency of aerogel, suitable for industrial thermal insulation, new energy flame retardant and other fields of large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of aerogel composite material modification technology, specifically relating to a method for preparing modified aerogel powder with fragmented pre-dispersion. Background Technology

[0002] Fiber-reinforced aerogel composites, with their excellent properties of low thermal conductivity, high temperature resistance, and aging resistance, are core materials in the field of high-end thermal insulation and flame retardancy. Through functional powder doping modification, infrared-shielding, wear-resistant, and high-temperature oxidation-resistant structures can be constructed within the aerogel system, effectively suppressing high-temperature radiative heat transfer in aerogels and improving structural stability and service life. This is a core technical means for the iterative upgrading of high-performance aerogels.

[0003] Currently, the commonly used powder composite modification process in the aerogel industry adopts the direct impregnation and doping mode of the whole fiber substrate, that is, the functional powder is directly mixed into the sol system and then impregnated into the whole shaped fiber aerogel substrate. This process has common technical pain points, which have long restricted the industrial application of high-performance aerogels: 1. Poor powder dispersibility and unstable light-shielding modification effect: Light-shielding powders such as silicon carbide and titanium dioxide have small particle size and high surface activity. Direct doping is prone to agglomeration, making it difficult to uniformly penetrate into the micro-nanopores of the intact fiber aerogel. Most of the powder only adheres to the material surface, resulting in uneven suppression of local radiative heat transfer in the aerogel, large fluctuations in high-temperature insulation performance, poor batch consistency, and inability to achieve a stable infrared light-shielding modification effect.

[0004] 2. Weak interfacial bonding of powder particles and easy failure at high temperatures: Aerogels have a dense pore structure and fixed pore size. The aggregated powder particles are large and cannot be embedded inside the three-dimensional network skeleton of the aerogel. They only rely on simple physical adsorption to adhere to the surface of the material. Under conditions of high-temperature airflow, thermal cycling, and repeated bending, the surface powder is very easy to fall off and be lost, resulting in a rapid decline in the high-temperature radiation insulation capacity of the aerogel and a significant reduction in the service life of the material.

[0005] 3. There is an inherent contradiction between modification and structural performance: Aerogel nanoporous framework structure is fragile. In order to increase the powder loading, traditional direct doping process requires increasing the powder dosage or extending the wetting time, which can easily block the aerogel nanopores and destroy the fiber-aerogel composite framework structure, resulting in loose, brittle materials and reduced mechanical strength. There is a technical contradiction between improving the light-blocking modification of powder and deteriorating the stability of aerogel structure, making it impossible to achieve both high performance and high stability.

[0006] Existing fiber fragmentation modification technologies simply break down and mix fiber substrates, failing to address the core issues of powder agglomeration, weak interfacial bonding, pore collapse, and performance imbalance. These technologies are characterized by weak innovation, low barriers to entry, and high substitutability, hindering the widespread application of high-performance aerogels. Summary of the Invention

[0007] To address the aforementioned problems, the present invention aims to provide a method for modifying and preparing fragmented pre-dispersed aerogel powders that overcomes the limitations of traditional direct doping of intact fiber substrates, simultaneously improves the functionality, structural stability, and batch consistency of aerogels, and possesses both process versatility and industrial-scale adaptability.

[0008] This invention is achieved through the following technical solution: A method for preparing modified fragmented pre-dispersed aerogel powder, characterized by comprising the following continuous process steps: S1. Powder pre-dispersion pretreatment: The modified powder is gradually added to the precursor sol and stirred at a constant temperature of 20~30℃ for no less than 30 minutes to break up the powder agglomeration and obtain a powder-sol mixture in which the powder particles are uniformly dispersed. S2. Fiber floc impregnation and composite: Fragmented fiber flocs are added in batches to the powder-sol mixture obtained in step S1, and the mixture is stirred continuously until all flocs are fully impregnated, so that the powder is adsorbed and embedded in the inner and outer pores of the fragmented fiber flocs, and the fiber-sol mixture system after impregnation and composite is obtained. S3. Gradient gel molding under pressure: Add a gel catalyst to the impregnated fiber-sol mixture, stir evenly, transfer to a gel tool, spread to a set thickness and cover with a cover plate, apply a constant pressure of 0.1~0.5MPa to maintain pressure and complete gradient gelation to obtain a gel-molded preform; S4. Graded solvent replacement soaking: The gel-molded preform is placed in industrial methanol with a mass fraction of 99% and soaked at a constant temperature of 20~30℃ for no less than 20 hours. The methanol solvent is replaced every 8 hours to remove the residual moisture in the gel-molded preform. S5. Supercritical drying and shaping: The gel-molded preform after solvent replacement is subjected to supercritical CO2 drying. The drying conditions are: temperature 50~60℃, pressure 12~16MPa, CO2 flow rate 2000~3000kg / h, and drying time 4~6h, to obtain a modified fiber-based aerogel composite material with three-dimensional uniform interlocking of powder.

[0009] Furthermore, the raw material ratio of the preparation system is as follows: the mass-volume ratio of fragmented fiber flakes to precursor sol is (50~60) g: (400~500) mL, and the mass of modified powder is 0.8%~1.2% of the mass of precursor sol.

[0010] Furthermore, the fragmented fiber flakes are one or more of glass fiber flakes, ceramic fiber flakes, high silica fiber flakes, carbon fiber flakes, and mullite fiber flakes; the fragmented fiber flakes are obtained by crushing a complete fiber substrate.

[0011] Furthermore, the precursor sol is selected from one or more of silica sol, zirconium oxide sol, alumina sol, phenolic sol, and polyimide sol.

[0012] Furthermore, the modified powder is one or more of the following: silicon carbide powder, titanium dioxide powder, iron oxide powder, carbon black powder, glass microspheres, boron nitride, alumina powder, copper powder, and nickel powder.

[0013] Furthermore, the gel catalyst is one or more combinations of ammonia, ammonium fluoride, ethylamine, ethanolamine, sodium hydroxide, potassium hydroxide, and epoxide.

[0014] Furthermore, in step S3, the constant pressure is provided by any one of a hydraulic device, a pneumatic device, or a counterweight loading device, and the pressure holding time is 10~30 minutes.

[0015] Furthermore, in step S1, the modified powder is added gradually in 3 to 5 batches, the stirring speed is controlled at 250 to 350 r / min, and the stirring is kept in a continuous stirring state throughout the process.

[0016] Further, in step S2, the fragmented fiber flocs are added to the powder-sol mixture in 2 to 3 batches, the stirring speed is controlled at 120 to 200 r / min, and the stirring time is 15 to 25 min.

[0017] Furthermore, in step S5, the conditions for supercritical CO2 drying are: temperature 50~60℃, pressure 12~16MPa, CO2 flow rate 2000~3000kg / h, and drying time 4~6h.

[0018] The beneficial effects of this invention are: Significantly improves powder dispersion uniformity: The pre-dispersion and pretreatment of powder breaks down the original agglomeration of ultrafine powder. Combined with the impregnation and composite of fragmented fiber flocs, the modified powder is uniformly embedded in the inner and outer pores of the fiber flocs and the three-dimensional network of aerogel in a single particle state. This avoids the problems of powder surface enrichment and local agglomeration in traditional processes, and realizes the uniform performance of powder doping modification effect in the overall space of the material.

[0019] Enhanced interfacial bonding strength of powder: During the pressure gradient gel molding process, the modified powder, fiber skeleton and aerogel are cross-linked and cured simultaneously. The powder is deeply embedded in the three-dimensional structure of the material, rather than simply physically adsorbed on the surface of the material. This effectively reduces the risk of powder falling off and being lost under high temperature airflow and hot and cold cycling conditions, and ensures the long-term effect of powder doping modification.

[0020] Balancing doping modification and structural performance: The powder is uniformly dispersed within the system, avoiding agglomerated powder from clogging the nanopores of the aerogel and damaging the framework structure; combined with pressure molding to enhance the bonding strength between flakes, while achieving effective powder loading and uniform doping, the mechanical strength of the material is maintained, alleviating the inherent contradiction between powder loading increase and material structure deterioration in traditional doping processes.

[0021] Wide range of process adaptability: It can be adapted to various types of modified powders and fiber substrates, and can achieve good dispersion and intercalation effects. It can prepare modified aerogel composite materials with different functions such as infrared light blocking, high temperature resistance, and conductivity according to the application requirements, and is suitable for industrial-scale production. Attached Figure Description

[0022] The present invention will now be described in further detail with reference to the accompanying drawings.

[0023] Figure 1 This is a process flow diagram of the method for preparing fragmented pre-dispersed aerogel powder modification according to the present invention. Figure 2 A schematic diagram of the morphology of silicon carbide powder-doped gel paper (5 mm) prepared by conventional methods; Figure 3 This is a schematic diagram of the morphology of silicon carbide powder-doped gel paper (5 mm) prepared by the fragmented pre-dispersed aerogel powder modification preparation method of the present invention. Detailed Implementation

[0024] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification.

[0025] It should be noted that the terms “comprising,” “including,” or any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0026] This comparative example uses the industry-standard direct impregnation and doping process of intact fiber substrate to prepare glass fiber-based aerogel paper. The raw material ratio is as follows: 54g of intact glass fiber paper, 450mL of silica sol (prepared with organosilicon grease), 5g of silicon carbide powder, and 15mL of ammonia catalyst.

[0027] Preparation steps: Silicon carbide powder is directly added to silica sol and stirred to obtain doped sol; intact glass fiber paper is immersed in the doped sol, fully wetted, and then removed and placed in a mold to gel naturally at room temperature; after gelation, the blank is placed in a 99% methanol solution and soaked at a constant temperature of 25℃ for 24 hours, with fresh methanol replaced every 8 hours; finally, it is dried for 5 hours at a temperature of 55℃, a pressure of 14MPa, and a CO2 flow rate of 2500kg / h to obtain silicon carbide doped aerogel paper prepared by conventional process.

[0028] The tensile strengths of glass fiber aerogel paper prepared by conventional doping methods are shown in Table 1: Table 1 Example 1

[0029] In this embodiment, silicon carbide-modified glass fiber-based silica aerogel composite material was prepared. The specific process is as follows: 54g of glass fiber fragments, 450mL of silica sol (prepared with organosilicon grease), and 5g of silicon carbide powder were weighed. The silicon carbide powder was selected as ultrafine light-shielding powder with a median particle size D50 of 1.0 to 2.0μm. 15mL of ammonia water was used as a catalyst.

[0030] Preparation steps: S1 Powder pre-dispersion: Silicon carbide functional powder is gradually added to silica sol according to the specified ratio, and stirred continuously at 300 r / min for 30 min at a constant temperature of 25℃ to break up powder agglomeration and obtain a powder-sol mixture with uniformly dispersed single powder particles; S2 Fragmented fiber impregnation: Broken glass fiber fragments are added to the mixture in batches and stirred continuously at 150 r / min for 20 min until the flakes are fully impregnated and suspended, with no unimpregnated dry fiber clumps; S3 Pressure gradient gelation: Ammonia catalyst is added dropwise and stirred rapidly for 1 min. n. Mix well, transfer to a gel fixture and spread to a thickness of 3 mm, cover with a cover plate and apply constant pressure for 10 min to complete the gradient cross-linking gel and obtain a gel-formed preform; S4. Graded solvent replacement: immerse the gel-formed preform in a 99% methanol solution at a constant temperature of 25℃ for 24 h, replacing with fresh methanol every 8 h to remove residual moisture and free sol; S5. Supercritical drying: dry for 5 h at a temperature of 55℃, a pressure of 14 MPa and a CO2 flow rate of 2500 kg / h to obtain a powder-modified aerogel composite material.

[0031] Performance test results: Thermal conductivity at room temperature: 0.01729 W / (m・k) Powder distribution: Three-dimensional uniform dispersion, no obvious agglomeration, no surface enrichment Cold and hot cycle stability (-40℃~600℃, 20 cycles): No obvious powder shedding or loss. Example 2

[0032] In this embodiment, titanium dioxide modified high-silica fiber-based silica aerogel composite material was prepared. The specific process is as follows: 60g of high-silica fiber fragments, 425mL of silica sol (prepared using inorganic silica sol), and 5g of titanium dioxide powder were weighed. The titanium dioxide powder was selected from rutile phase with a particle size D50 of 0.8-1.5μm. The catalyst was selected from ammonium fluoride, and the amount used was 80mL.

[0033] Preparation steps: S1 Powder pre-dispersion: Add titanium dioxide anti-aging functional powder to the silica sol system step by step according to the formula, stir at 300 r / min for 30 min to break up powder agglomeration and prepare a uniform and stable powder-sol mixture; S2 Fiber impregnation and composite: Add high silica fiber fragments to the mixing system in batches, stir at 150 r / min for 20 min until all flakes are fully impregnated and there are no unimpregnated dry fiber clumps; S3 Pressure gel forming: Add the specified amount of ammonium fluoride catalyst and stir rapidly. After mixing thoroughly, the mixture is transferred to a tooling and spread evenly to a thickness of 3 mm. A constant pressure is applied and maintained for 10 minutes to achieve gradient slow gelation and obtain a gel-formed preform. S4 Solvent replacement and shaping: The preform is placed in 99% methanol and soaked at a constant temperature of 25°C for 24 hours. The solution is changed every 8 hours to completely replace the residual solvent and moisture inside and stabilize the aerogel nanoporous structure. S5 Supercritical drying: The preform is dried for 5 hours using parameters of 55°C, 14 MPa, and CO2 flow rate of 2500 kg / h.

[0034] Performance test results: Thermal conductivity at room temperature: 0.01650 W / (m・K); Powder distribution: Firmly bonded, with no localized accumulation. Example 3

[0035] In this embodiment, boron nitride modified mullite fiber-based alumina aerogel composite material was prepared. The specific process is as follows: 58g of mullite fiber fragments, 475mL of alumina sol (prepared with aluminum chloride), and 4.5g of boron nitride powder were weighed. The boron nitride powder used was hexagonal boron nitride with D50 = 1.0~3.0μm, and the catalyst used was propylene oxide, with an addition amount of 10g.

[0036] Preparation steps: S1 High-temperature powder pre-dispersion: Add the specified amount of propylene oxide as a catalyst to the alumina sol dropwise and stir vigorously for 5 minutes; add boron nitride high-temperature resistant and antioxidant powder gradually to the alumina sol system according to the specified ratio, and stir at 350 r / min for 35 minutes at room temperature to break up the agglomeration of ultrafine powder and form a uniform and stable high-temperature powder-alumina sol mixture; S2 High-temperature resistant fiber impregnation: Use mullite fiber fragments to flocculentize and add them to the mixing system in batches, stirring at 180 r / min. Stir for 25 minutes to fully impregnate the powder, allowing the high-temperature powder to be deeply embedded in the three-dimensional pores of the fiber; S3 Pressure gel molding: Spread the mixture evenly to a thickness of 10 mm, apply constant pressure, and place it in a 70℃ water bath for 20 minutes to complete the gelation and obtain a gel-molded preform; S4 Solvent replacement: Soak in methanol at 25℃ for 24 hours, changing the solution every 8 hours to fully replace the polar solvent; S5 Supercritical drying: Dry using standard process for 5 hours to obtain powder-modified alumina aerogel composite material.

[0037] Performance test results: Thermal conductivity at room temperature: 0.01897 W / (m・K); Linear shrinkage at ultra-high temperature (1000℃): 1.5%; Powder distribution: Uniformly filled powder with dense interfacial bonding and no shedding; 10mm thick sample, heated at 1300℃ for 30 min: Back temperature 304℃. Table 2 below shows the performance test results of the glass fiber-based aerogel paper prepared by the method of this invention: Table 2

[0038] From Table 1, Table 2 and Figure 2 , Figure 3 The comparison shows that, thanks to the enhanced bonding strength between the flocs by pressure gel molding, the aerogel paper prepared by this invention has a tensile strength that is basically equivalent to that of samples prepared by conventional processes, and the mechanical properties of the material are not significantly degraded due to powder modification; at the same time, the uniform dispersion of the powder makes the overall thermal conductivity of the material better and the thermal insulation performance more stable.

[0039] The scope of protection of this invention is not limited to the technical solutions disclosed in the specific embodiments. Any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of this invention shall fall within the scope of protection of this invention.

Claims

1. A method for preparing modified fragmented pre-dispersed aerogel powder, characterized in that: The process includes the following continuous steps: S1. Powder pre-dispersion pretreatment: The modified powder is gradually added to the precursor sol and stirred at a constant temperature of 20~30℃ for no less than 30 minutes to break up the powder agglomeration and obtain a powder-sol mixture in which the powder particles are uniformly dispersed. S2. Fiber floc impregnation and composite: Fragmented fiber flocs are added in batches to the powder-sol mixture obtained in step S1, and the mixture is stirred continuously until all flocs are fully impregnated, so that the powder is adsorbed and embedded in the inner and outer pores of the fragmented fiber flocs, and the fiber-sol mixture system after impregnation and composite is obtained. S3. Gradient gel molding under pressure: Add a gel catalyst to the impregnated fiber-sol mixture, stir evenly, transfer to a gel tool, spread to a set thickness and cover with a cover plate, apply a constant pressure of 0.1~0.5MPa to maintain pressure and complete gradient gelation to obtain a gel-molded preform; S4. Graded solvent replacement soaking: The gel-molded preform is placed in industrial methanol with a mass fraction of 99% and soaked at a constant temperature of 20~30℃ for no less than 20 hours. The methanol solvent is replaced every 8 hours to remove the residual moisture in the gel-molded preform. S5. Supercritical drying and shaping: The gel-molded preform after solvent replacement is subjected to supercritical CO2 drying. The drying conditions are: temperature 50~60℃, pressure 12~16MPa, CO2 flow rate 2000~3000kg / h, and drying time 4~6h, to obtain a modified fiber-based aerogel composite material with three-dimensional uniform interlocking of powder.

2. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: The raw material ratio of the preparation system is as follows: the mass-volume ratio of fragmented fiber flocs to precursor sol is (50~60) g: (400~500) mL, and the mass of modified powder is 0.8%~1.2% of the mass of precursor sol.

3. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: The fragmented fiber flakes are one or more of glass fiber flakes, ceramic fiber flakes, high silica fiber flakes, carbon fiber flakes, and mullite fiber flakes; the fragmented fiber flakes are obtained by crushing a complete fiber substrate.

4. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: The precursor sol is selected from one or more of silica sol, zirconium oxide sol, alumina sol, phenolic sol, and polyimide sol.

5. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: The modified powder is one or more of the following: silicon carbide powder, titanium dioxide powder, iron oxide powder, carbon black powder, glass microspheres, boron nitride, alumina powder, copper powder, and nickel powder.

6. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: The gel catalyst is one or more combinations of ammonia, ammonium fluoride, ethylamine, ethanolamine, sodium hydroxide, potassium hydroxide, and epoxides.

7. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: In step S3, the constant pressure is provided by any one of a hydraulic device, a pneumatic device, or a counterweight loading device, and the pressure holding time is 10~30 minutes.

8. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: In step S1, the modified powder is added gradually in 3 to 5 batches, and the stirring speed is controlled at 250 to 350 r / min. The stirring is kept continuous throughout the process.

9. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: In step S2, the fragmented fiber flocs are added to the powder-sol mixture in 2 to 3 batches, the stirring speed is controlled at 120 to 200 r / min, and the stirring time is 15 to 25 min.

10. The method for preparing a fragmented pre-dispersed aerogel powder according to claim 1, characterized in that: In step S5, the conditions for supercritical CO2 drying are: temperature 50~60℃, pressure 12~16MPa, CO2 flow rate 2000~3000kg / h, and drying time 4~6h.